Influência de antifúngicos ambientais sobre a tolerabilidade aos antifúngicos clínicos, morfo-fisiologia e virulência em Cryptococcus gattii e C. neoformans - Rafael Wesley Bastos (2018)
Cryptococcus gattii and C. neoformans are the main etiological agents of cryptococcosis. Because these pathogens are found associated with plants and due to the increased use of agrochemicals, in this work we evaluated the hypothesis that exposure to environmental antifungal could affect tolerance to clinical antifungal and virulence of Cryptococcus spp. Exposure to agrochemicals tebuconazole (TBZ) and pyraclostrobin (PCT) increased the tolerance (cross-resistance) of some C. gattii and C. neoformans strains to fluconazole (FCZ), itraconazole and ravuconazole. The same effect did not happen when metalaxyl was used. Some strains presented cross-resistance to clinical azoles even after contact with agrochemicals had ceased. In addition to altering antifungal tolerance, TBZ and PCT caused changes in the morphology of Cryptococcus, with some strains forming pseudohyphae in contact with agrochemicals. Cells of C. gattii R265 and C. neoformans H99 exposed to TBZ were less virulent in murine model than non-exposed cells. However, cells recovered from animals infected with cells previously exposed to TBZ maintained the increased tolerance to clinical azoles. In addition, treatment with FCZ was not able to decrease the fungal load in the lung of animals infected with TBZ-exposed cells. Increased antifungal tolerance may be explained by increased expression of ERG11 and efflux pumps, PDR11 (AFR1) and MDR1. Regarding PCT exposure, C. gattii R265 cells exposed to PCT and then cultured in medium without the drug for 10 passages (10p cells) were less virulent in a murine animal model, and treatment with FCZ was ineffective in animals infected with these cells, unlike what happened to animals infected with non-exposed cells. Transcriptomic analysis of 10p and non-exposed cells showed that increased tolerance can be attributed to increased expression of efflux pumps and the reduction of virulence could be attributed to lower expression of genes involved in acquisition of ions pathway. It is concluded, therefore, that the exposure to the agrochemicals TBZ and PCT increases tolerance to clinical azoles, alters the morphology and decreases the virulence of Cryptococcus gattii and C. neoformans.